Book review: Autobiography of my dead brother. Walter Dean Myers (author) and Christopher Myers (illustrator). - Angus Norquay (Scottish Journal of Residential Child Care, 2009)
Autobiography of my dead brother portrays the life of teenage Jesse, living in the ganglands of Harlem, downtown New York. As Jesse matures into another anonymous black teenager, he finds his life divided. Childhood friendships, traditional family values and church on the one hand, clash with the demands of 'being in the 'hood', gang warfare, guns and drugs on the other. Walter Dean Myer's graphic novel highlights the daily realities of being a black teenager in the city, and the fear and danger that have to be overcome to stay alive.